2012
DOI: 10.4209/aaqr.2011.11.0209
|View full text |Cite
|
Sign up to set email alerts
|

Particle Resuspension in School Gyms during Physical Activities

Abstract: The aim of this work was to quantify the exposure of children to particle resuspension in school gyms. In fact, although moderate standard aerobic activity is suggested for good health, adverse health effects could affect people exercising in micro-environments with ambient pollution. Overall, 12 micro-environments were chosen and analyzed in a 3-month experimental campaign. The different fractions of particulate matter (PM) were measured by means of photometers, calibrated for the specific aerosols studied th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…In the same study, the I/O ratio was below 0.5 with the indoor PM 10-2.5 varied between 0.5-4.9 µg m -3 during weekends and holidays. In another study, Buonanno et al (2012) confirmed that the PM 10-2.5 emission factors in the range of 1.5-8.9 mg min -1 during exercising activities of pupils inside a school gym. These re-suspension rates were slightly higher than those presented by Ferro et al (2004) as 0.03-0.5 mg min -1 for PM 2.5 and 0.1-1.4 mg min -1 for PM 5 .…”
Section: Re-suspension Emission Ratesupporting
confidence: 64%
See 3 more Smart Citations
“…In the same study, the I/O ratio was below 0.5 with the indoor PM 10-2.5 varied between 0.5-4.9 µg m -3 during weekends and holidays. In another study, Buonanno et al (2012) confirmed that the PM 10-2.5 emission factors in the range of 1.5-8.9 mg min -1 during exercising activities of pupils inside a school gym. These re-suspension rates were slightly higher than those presented by Ferro et al (2004) as 0.03-0.5 mg min -1 for PM 2.5 and 0.1-1.4 mg min -1 for PM 5 .…”
Section: Re-suspension Emission Ratesupporting
confidence: 64%
“…For example, re-suspension is affected by human foot motion such as walking and foot tapping, which also redistribute particulate matter on a surface (Kubota and Higuchi, 2013). A strong correlation appears between the number of individuals and the particle re-suspension (Buonanno et al, 2012). Moreover, carpets are potentially more significant with higher resuspension rates in comparison to smooth and bare floors (Shaughnessy and Vu, 2012).…”
Section: Re-suspension Emission Ratementioning
confidence: 99%
See 2 more Smart Citations
“…The main reason of high concentration of PM 1.0 in classrooms was resuspension of of PM due to the students' movements. Buonanno et al (2012b) characterized there suspension of particles in school gyms and concluded that student activity was the main predictor of particle resuspension and among the various PM fractions, coarse particles (PM 2.5 and PM 10 ) were found to be the most relevant. Guo et al (2010) did not find any influence on indoor PM 2.5 concentrations of the number of students in the classroom, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%